T2SS-peptidase XcpA associated with LasR evolutional phenotypic variations provides a fitness advantage to Pseudomonas aeruginosa PAO1 - Cheng, Mengmeng; Chen, Ruiyi; Liao, Lisheng (Frontiers in Microbiology, 2023)
The Gram-negative opportunistic pathogen Pseudomonas aeruginosa possesses hierarchical quorum sensing (QS) systems. The intricate QS network of P. aeruginosa synchronizes a suite of virulence factors, contributing to the mortality and morbidity linked to the pathogenicity of this bacterium. Previous studies have revealed that variations in the lasR gene are frequently observed in chronic isolates of cystic fibrosis (CF). Specifically, LasRQ45stop was identified as a common variant among CF, lasR mutants during statistical analysis of the clinical lasR mutants in the database. In this study, we introduced LasRQ45stop into the chromosome of P. aeruginosa PAO1 through allelic replacement. The social traits of PAO1 LasRQ45stop were found to be equivalent to those of PAO1 LasR-null isolates. By co-evolving with the wild-type in caseinate broth, elastase-phenotypic-variability variants were derived from the LasRQ45stop subpopulation. Upon further examination of four LasRQ45stop sublines, we determined that the variation of T2SS-peptidase xcpA and mexT genes plays a pivotal role in the divergence of various phenotypes, including public goods elastase secretion and other pathogenicity traits. Furthermore, XcpA mutants demonstrated a fitness advantage compared to parent strains during co-evolution. Numerous phenotypic variations were associated with subline-specific genetic alterations. Collectively, these findings suggest that even within the same parental subline, there is ongoing microevolution of individual mutational trajectory diversity during adaptation.